2022
DOI: 10.3390/w14213577
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Rates and Modes of Landslide Colluvium Removal in River Channels of Podhale (Western Carpathians)

Abstract: This paper presented some hydrological factors affecting the course and rate of fluvial erosion of landslide colluvium at its contact with river flow. Volumes of colluvium eroded by rivers in the period 2013–2019 were measured at Podhale (a part of Polish West Carpathians) on four landslides representing various geological settings. At each landslide, changes in shape and position of the contact zone between colluvium and river water were registered after episodes of high river stage. The obtained data on chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Landslides that remain in contact with stream channels are constantly active, as they are under the influence of continuous fluvial erosion 44 . The intensity of colluvium erosion near the rivers in the Outer Carpathians was found to be strongly dependent on the water levels in the adjacent stream 45 . We also observed a similar phenomenon, with a significant number of landslides in the immediate vicinity of watercourses in the Gorce National Park study area.…”
Section: Discussionmentioning
confidence: 96%
“…Landslides that remain in contact with stream channels are constantly active, as they are under the influence of continuous fluvial erosion 44 . The intensity of colluvium erosion near the rivers in the Outer Carpathians was found to be strongly dependent on the water levels in the adjacent stream 45 . We also observed a similar phenomenon, with a significant number of landslides in the immediate vicinity of watercourses in the Gorce National Park study area.…”
Section: Discussionmentioning
confidence: 96%
“…On the falling limb, the river water continued to erode the colluvial layer as the pore water drained during a rapid fall of the flood wave when the river is mainly recharged through baseflow. Rise in the groundwater level through infiltration within landslides after a rainfall event also led to the reactivation of slope failure and increased the supply of colluvium to the channels (Kukulak et al, 2022). In another exampl e from a small stream in the Mid-Atlantic USA, Rose et al (2018) observed the combination of OW and US loading during an extreme climate event (ECE).…”
Section: (Continued)mentioning
confidence: 99%